Analisis Kandungan Gula Pada Minuman Kekinian Thai Tea, Milk Boba dan Ice Tea Di UIN Jakarta - Nita Rosita (Journal of Natural Sciences, 2023)
Study about the analysis of sugar content in popular drinks around UIN Jakarta has been carried out. The purpose of this study was to determine the sugar content of glucose and sucrose in popular drinks. This type of research is quantitative research. The method used is descriptive analysis. The number of samples taken was 10 consisting of Thai tea drinks, boba milk, sweet iced tea taken from sellers around UIN Jakarta. The results showed that the sugar content of glucose was between 5-66,5 grams, while the results of the sucrose test contained between 1-26 grams and the total sugar content of contemporary drinks was between 23-70 grams. The results showed that there were 2 samples of contemporary drinks that exceeded the recommended intake of 50 grams of sugar per day according to Minister of Health Regulation No. 30 year 2013.